(untitled) (Global Journal of Human-Social Science, 2012)
Deemed as depictions of dejection intermingled with penetrative multiaccentuality nothingness and murkiness Beckett s multilayered texts lead the mind of the reader observer into a deadlock in rendering a plausible connotation camouflaged in their sub-texts As a result the paradoxical and baffling amalgamation of simplicity and complexity in his works keeps the readers and pundits captivated in the fanciful web of the text Expectedly this delusive feature has tantalized a bumper crop of articles to mark Beckett down as a paragon of absurdism and atheism over the past few decades However by ploughing new fields and charting new territories of his works we can redefine and re-delineate Beckett s ideologies as non-absurdist and theist and ultimately he himself as an absurdistic writer rather than an absurdist author Contrary to the mainstream impression of hermeneutists about Beckett s rationalizations that are fallaciously thought to be absurd and purposeless his argumentations of absurdity are not a stymie to propagandize absurdism but an initiative to actuate our consciousness to eschew our absurd life in order to lead us to a new sphere of reality and meaning Therefore this paper is to underpin the above-mentioned avowals by re-introducing Beckett as a crusader against absurdity and mental stagnation through a comparative review of Rough for Theatre I and II